"Batekang Hambaruan" as the Meaning of Mental Health in Dayak Culture - Nurika Salsabila; Ainurizan Ridho Rahmatulloh (Journal of Social Research, 2026)
Mental health in Indigenous Peoples is often understood through clinical frameworks, thus ignoring the local meanings inherent in culture. This study aims to uncover the meaning of mental health in Dayak culture through the concept of Batekang Hambaruan as a form of inner strength. The study uses a qualitative phenomenological approach, involving participants from the sub-tribes Dayak Ngaju and Dayak Barai in Kalimantan. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis. The results showed that mental health is defined as an individual’s ability to recover, think clearly, work, and perform meaningful life roles amid life’s stresses. In contrast, the condition of Balemu Hambaruan or Mamau is understood as a temporary phase of mental weakness. Mental vulnerability is influenced by economic, structural, and social labeling pressures, while mental reinforcement is shaped by cultural values such as Isen Mulang and Pintar Harati, indigenous practices, and family and community support. These findings indicate that Batekang Hambaruan represents a form of culture-based resilience in interpreting and maintaining the mental health of the Dayak community, emphasizing the importance of a culturally informed mental health approach for Indigenous communities.